Post-stroke aphasia in famous writers: when Neurology left geniuses speechless - VITTURI, Bruno Kusznir; GAGLIARDI, Rubens José (Arquivos de Neuro-Psiquiatria, 2021)
Aphasia is a frequent and devastating stroke complication that does not spare even great writers. In these cases, not only one of the highest cognitive functions is suddenly lost but also the act of bringing beauty into the world. Herein, we discuss the case of three writers who had to abandon their art compulsorily due to a cerebrovascular disease: Charles Baudelaire, Ralph Waldo Emerson, and Stendhal. They were magnificent writers, united by excellence in literature and an inevitable destiny that restricted their art to just a few words. They are also examples of the proximity of Neurology to Art, History, and Literature.
Keywords: Neurology; Stroke; Aphasia; Art